End-to-end quality of service support for multimedia applications in the Internet. - Sallabi, Farag M. (University of Ottawa (Canada), 2002)
Quality of Service (QoS) in the Internet is one of the most active research areas in recent years. With the introduction of sophisticated multimedia applications, researchers have concentrated in finding solutions to make the Internet a suitable environment for such applications. The obvious solution is to enable applications reserve network resources according to their QoS needs. Researchers have also suggested enhancing the existing routing protocols for handling QoS. In this thesis, we present an end-to-end QoS architecture based on resource reservations. The architecture proposes the introduction of domain agencies in network domains. The domain agency is responsible for managing the resources in its domain and reserve resources according to the received requests from the users. It handles immediate and advance resource reservations and adapts the reserved resources according to user interactions. It contains a QoS routing agent to construct a QoS intra-domain path. The QoS routing agent uses a modification of Dijkstra's algorithm to find a shortest-narrowest path that accommodates the requested QoS. We present the analytical study and implementation of the main components proposed in this thesis. Then we present implementation of the architecture in an agent environment, which provides a good opportunity to test and analyze the system.
Keywords: Engineering, Electronics and Electrical.